TERORRISM OF THE IRISH REPUBLIACN ARMY (Heritage, 2024)
The Irish Republican Army (IRA) is one of the most renowned and long-standing terrorist organizations in modern history. Founded in the early 20th century, this group employed various forms of violence and terrorism to achieve its political goals. This paper analyzes the evolution of the IRA, its tactics, ideology, and impact on the political landscape of Ireland and beyond. Through the examination of historical sources, documents, and secondary literature, the study provides a comprehensive overview of the IRA's development from its establishment in 1919, through the period known as "The Troubles" in the late 20th century, to its eventual split into several factions and the ceasefires of the 1990s. Human history is marked by various forms of terrorist activities, and terrorism can be seen as a characteristic of nearly all epochs of human civilization. This era, in particular, is marked by ethno-separatist terrorism, making the explanation of this type of terrorism and the depiction of the history of the conflict in Ireland, with a special focus on the origin, goals, methods, and structure of the IRA and its long-standing terrorist activities in Northern Ireland, the central theme of this academic paper. The conclusion emphasizes the significance of the IRA in the context of Ireland's struggle for independence and its long-term impact on the peace process in Northern Ireland. It also examines how the IRA's experience can contribute to a better understanding of the phenomenon of political violence and terrorism in the contemporary world. This paper provides a thorough analysis that may serve as a foundation for further research in the fields of political violence, terrorism, and peace processes.
Keywords: terrorism, Irish Republican Army, Provisional Irish Republican Army, Official Irish Republican Army, ethno-separatism